Selenium and silver nanoparticles: A new approach for treatment of bacterial and viral hepatic infections via modulating oxidative stress and DNA fragmentation. Issue 3 (29th December 2021) - Gad, Sameh S.; Abdelrahim, Dina S.; Ismail, Sameh H.; Ibrahim, Sherine M.
Abstract: Nanoparticles are recently playing a potential role in improving drug uptake and the treatment of diseases. A variety of nanoparticles, such as selenium nanoparticles (SeNPs) and silver nanoparticles (AgNPs) have been used as drug carriers in various ways for treatment of cancers and liver diseases. Our aim in this study is to investigate the ability of AgNPs and SeNPs to target and treat the viral and bacterial infection of the liver in rats and cell lines. For assessment of antioxidant activity of AgNPs in rats with induced liver bacterial infection, six adult male albino rats were included in this study, liver slices were taken and assigned to 6 groups. Markers of hepatic functions, oxidative stress, and inflammation in liver slices are carried out. Although for assessment of antiviral activity of SeNPs, hepatitis B virus transfected (HBV)‐replicating human cell line HepG2 and normal hepatocyte cells were used, hepatic and inflammatory alterations are determined through quantitative polymerase chain reaction and comet assay techniques. The effect of AgNPs on interleukin‐6 and tumor necrosis factor levels were reduced in different treated groups with AgNPs compared with the control and diseased groups. On the other hand, SeNPs revealed significant alterations in the inflammatory markers as well as DNA damage in the treated HBV‐human cell line HepG2 compared to the diseased ones. AgNPs have the ability for producing various hepatic alterations and can inhibit the proliferation of hepatic stellate cells (HSCs) in a dose and size‐dependent manner. On the other hand, SeNPs showed excellent selectivity towards viral cells in the HepG2 cell lines. Both AgNPs and SeNPs might be promising drug designs for treating viral and bacterial liver diseases.